Clinical significance of the combined test of seven blood coagulation indexes, lipids and platelet agglutination on hypercoagulable state of blood in parturient women - Zhang, Wenjuan; Yu, Tao; Wang, Yunshuang; Hu, Meili; Gao, Tianxiang (Pakistan journal of medical sciences, 2024)
Objective: To investigate the value of the combined test of seven blood coagulation indexes, lipids and platelet agglutination on the evaluation of the hypercoagulable state of blood in parturient women. Methods: This is a retrospective study. Total 50 high risk parturient women who underwent an antenatal examination in Baoding Maternal and Child Health Hospital from June 2021 to January 2023 were selected as the observation group, while 50 normal parturient women who underwent antenatal examination without comorbidities and complications were randomly collected in a ratio of 1:1 as the control group. All subjects had venous blood drawn for testing of seven blood coagulation indexes, lipids and platelet agglutination before delivery, and their general data were recorded. Results: The activated partial thromboplastin time(APTT) in the observation group was lower than that in the control group, while thrombin time(TT) and D-dimer(DD) were both higher than those in the control group, with statistically significant differences(p<0.05); total cholesterol (TC) and triglyceride (TG) in the observation group were both higher than those in the control group, with statistically significant differences (p<0.05); adenosine diphosphate (ADP) and arachidonic acid (AA) in the observation group were both higher than those in the control group, with statistically significant differences (p<0.05). Moreover, the overall incidence of adverse pregnancy was higher in the observation group than in the control group, with a statistically significant difference (p<0.05). Conclusions: The combined test of seven blood coagulation indexes, lipids and platelet agglutination results in excellent performance in predicting and judging the presence or absence of the hypercoagulable state of blood in parturient women, with the combination of APTT+TT+DD+TG+ADP+AA being the preferred test. doi: https://doi.org/10.12669/pjms.40.4.7530 How to cite this: Zhang W, Yu T, Wang Y, Hu M, Gao T. Clinical significance of the combined test of seven blood coagulation indexes, lipids and platelet agglutination on hypercoagulable state of blood in parturient women. Pak J Med Sci. 2024;40(4):741-746.  doi: https://doi.org/10.12669/pjms.40.4.7530 This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.